O programa de compliance e suas implicações no cerne da responsabilidade empresarial : estudo comparado Brasil versus EUA - Weber, Mark (2017)
The purpose of this study is basically focused on the attempt to understand, analyze and promote a deep debate around the importance of compliance programs into the corporate ambience as way of preventing illicit practices committed inside the several social structures. Foreign and national legislation is taken as base surrounding the subject in a preventive and repressive bias of state actions and the state-private relation. The main concern of the research is over the questioning on current regulation patterns and compliance program establishing in Brazil compared to other legal systems specially regarding the consequences in corporate core responsability in national scope. As work methodology, the debate about patterns of action is developed into the compliance programs, with the objective of checking whether or not they are able to function as objective parameters to mark out the demands and responsibilities attributed to the individual or corporation in the ambience called corporate offense. The experience of compared laws is searched through the laws of the countries with more expertise on the subject (in case of the USA), without neglecting our internal anti-corruption legislation. The hypothetical-deductive method is chosen in the restless quest for cleaner and safer answers to the problem. As for the kind of research, this is an exploratory activity of bibliographic characteristic, with qualitative approach.